Translation and Construct Validity of the Feeling Scale and the Felt Arousal Scale in Portuguese Recreational Exercisers - Brito, Henrique; Teixeira, Diogo; Araújo, Duarte (Cuadernos de Psicología del Deporte, 2022)
Feeling Scale and Felt Arousal Scale are widely used in sport research. They provide a practical assessment of self-reported affect and arousal during exercise. The original scales were translated from English to Portuguese. Afterward, it was tested if the affect and arousal scores in the picture-based Self-Assessment Manikin predicted the scores in the Feeling Scale and the Felt Arousal Scale in 47 Portuguese recreational exercisers, before and after an exercise session. Self-Assessment Manikin showed moderate-to-strong correlations with the Feeling Scale (r = 0.70 and r = 0.56, p < 0.01) and the Felt Arousal Scale (r = 0.65 and r = 0.72, p < 0.01), and substantial predictive power over the Feeling Scale (R2 = 47% and R2 = 31%) and the Felt Arousal Scale (R2 = 42% and R2 = 52%). The Feeling Scale and Felt Arousal Scale are valid instruments to measure affect and arousal in Portuguese exercisers.